THE POTENTIAL POSITION OF THE YUAN AND RUBEL CURRENCY TO REPLACE THE AMERICAN DOLLAR AS THE WORLD'S STRONGEST CURRENCY - Natallios Peter Sipasulta; Anacostia Kowanda; Dionysia Kowanda (Asosiasi Dosen Muda Indonesia, 2023)
It has been decades where world trade is controlled and dominated by the power of the American dollar currency as the world's main currency in carrying out and conducting world trade transactions, until one day when the American president named Richard Nixon stated that the American dollar currency was no longer become the main currency in world trade, and the countries of the world can use their currency to trade freely. Then it was discovered and developed the Swift system which was eventually used as a weapon by the United States to carry out a world trade pattern where the American dollar remained the currency used by countries around the world to make sales and purchases of goods they needed each other because they must use the Swift system in transactions, especially for the purchase of oil produced by the state of Saudi Arabia. Whether Russia and China can replace the strength of the US dollar with the yuan and ruble in the not too distant future, some of the possibilities examined in this journal will facilitate our understanding of this possibility, although there is still much work to be done by Russia and China. to be able to realize their plan to replace the strength of the US dollar with the yuan and the ruble.